2017
DOI: 10.1002/nau.23197
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva versus straining: There is a distinct difference in resulting bladder neck and puborectalis muscle position

Abstract: Valsalva and straining are different tasks with different PFM activation patterns. The PF is stiffer with Valsalva resulting in better BN support whereas straining leads to more PR and BN descent. These terms should not be used interchangeably and women have to be instructed carefully to allow appropriate interpretation of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…16 Participants were also instructed how to perform a maximal straining maneuver, by pushing as much as possible against a closed glottis, as if defecating. 17 Before data acquisition with the FemFit®, the device was covered with a condom, lubricated with hypoallergenic gel, and inserted into the participant's vaginal cavity, in an anterior-posterior axis by the assessor. Further, to ensure comfort and familiarization with the device and procedure, participants were asked to perform three unrecorded PFM contractions.…”
Section: First Sessionmentioning
confidence: 99%
“…16 Participants were also instructed how to perform a maximal straining maneuver, by pushing as much as possible against a closed glottis, as if defecating. 17 Before data acquisition with the FemFit®, the device was covered with a condom, lubricated with hypoallergenic gel, and inserted into the participant's vaginal cavity, in an anterior-posterior axis by the assessor. Further, to ensure comfort and familiarization with the device and procedure, participants were asked to perform three unrecorded PFM contractions.…”
Section: First Sessionmentioning
confidence: 99%
“…For instance, abdominal straining leads to the relaxation of pelvic floor muscle which favors urinary incontinence in women. 28 The observation of Plevnick 29 that the increase of abdominal pressure acts opening the bladder neck is another argument in favor. Additionally, Hasegawa et al 30 suggested that the patients who urinate with straining sometimes suffered from SUI.…”
Section: Discussionmentioning
confidence: 99%
“…11 During Valsalvaforced expiration against a closed glottis-the PFM move cranially (15 mm) or slightly caudally (2 mm) and during straining-strain as if defecating with relaxed PFM-the PFM displace caudally (8-15 mm). 12,13 Incontinent women show an extended amount of caudal displacement. 13 During coughing, the anterior and posterior urethra, as well as the anorectal angle displacement has been described in a ventral caudal for the continent and dorso caudal direction for incontinent women with maximum displacement varying from 4 to 12 mm.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Incontinent women show an extended amount of caudal displacement. 13 During coughing, the anterior and posterior urethra, as well as the anorectal angle displacement has been described in a ventral caudal for the continent and dorso caudal direction for incontinent women with maximum displacement varying from 4 to 12 mm. 14 PFM displacement is mainly investigated during coughing, Valsalva, straining, and voluntary PFM contraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation